Developing an objectives hierarchy for multicriteria decisions on land use options, with a case study of biodiversity conservation and forestry production from Papua, Indonesia. Issue 3 (May 2017) - Sarkar, Sahotra; Dyer, James S; Margules, Chris; Ciarleglio, Michael; Kemp, Neville; Wong, Grace; Juhn, Daniel; Supriatna, Jatna
A framework was developed for the construction of an objectives hierarchy for multicriteria decisions in land use planning. The process began through identification of fundamental objectives; these were iteratively decomposed into a hierarchy of subobjectives until a level was reached at which subobjectives had measurable attributes. Values were derived for attributes through a variety of methods and weights assigned to objectives through preference elicitation. The framework assumed that the objectives could be incorporated into a linear value function; this required attributes to satisfy preference and difference independence conditions. Strategies were developed to address typical features that distinguish land use decisions from many other multicriteria decisions. The methodology was illustrated with a case study of land use planning in a forestry concession in the Merauke region of Papua Province, Indonesia. The problem involved severe hard constraints; the analysis showed how these can be accommodated within the framework. Results integrated interests and preferences of a diverse set of stakeholders (resident peoples, developers, and conservation professionals) and were intended for implementation. This methodology is extendible to other land use problems.